INVESTIGATION OF SYNERGIC/ANTI-SYNERGIC INTERACTIONS OF DIHYDROXIFUMARIC ACID AND ASCORBIC ACID WITH DPPH - VICOL, Crina; CIMPOIU, Claudia; DUCA, Gheorghe (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Reaction of the free-radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) with dihydroxyfumaric acid (DHF) and ascorbic acid (AA) was investigated in ethanolic media and in wine simulated matrix by using a stopped-flow system. The antioxidant activity for both acids were significantly higher in wine matrix, the observed constants (kobs) being about 3 s-1 for DHF and 0.66 s-1 for AA. Synergic and anti-synergic interactions of DHF and AA against DPPH were also investigated. A strong anti-synergic effect was noticed in ethanol (kobs < 0.35 s-1). In wine simulated matrix the constants were higher than in ethanol (kobs ≈ 1 s-1), but still too small for a synergic effect. Some explanations concerning the mechanisms of antioxidant action are proposed.